2014
DOI: 10.1089/dna.2013.2247
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Association ofInterleukin-18Gene Polymorphisms with Primary Immune Thrombocytopenia in a Chinese Han Population

Abstract: Interleukin-18 (IL-18) is an inflammatory cytokine that plays an important role in autoimmune disease by inducing interferon-g secretion. Considering the abnormal serum concentration of IL-18 in primary immune thrombocytopenia (ITP) patients and the regulated effect of IL-18 gene polymorphisms on its production, the aim of this study was to investigate a possible association between the IL-18 promoter polymorphisms ( -137 G/C and -607 C/A sites) and genetic susceptibility to ITP in a Chinese Han population. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…23,24 In our study, we found that there was no significant difference between the ITP patients and the control group as regard to the IL-18 genotype polymorphism. This in agreement with Zhao et al 25 and Li et al 26 who stated that there is no association between IL-18 promotor polymorphism and occurrence of primary thrombocytopenia.…”
Section: Discussionsupporting
confidence: 92%
“…23,24 In our study, we found that there was no significant difference between the ITP patients and the control group as regard to the IL-18 genotype polymorphism. This in agreement with Zhao et al 25 and Li et al 26 who stated that there is no association between IL-18 promotor polymorphism and occurrence of primary thrombocytopenia.…”
Section: Discussionsupporting
confidence: 92%